2022
DOI: 10.3389/fphar.2022.817237
|View full text |Cite
|
Sign up to set email alerts
|

The TNF-Alpha Inducing Protein is Associated With Gastric Inflammation and Hyperplasia in a Murine Model of Helicobacter pylori Infection

Abstract: Helicobacter pylori (H. pylori) is a Gram-negative bacterium that colonizes the human stomach leading to the development of chronic gastritis, peptic ulcers and gastric adenocarcinoma. A combination of host, environment and bacterial virulence factors contribute to disease development. The H. pylori TNFα inducing protein (Tipɑ) is a virulence factor shown to induce multiple pro-inflammatory cytokines in addition to TNFα in vitro. The goal of the present study was to elucidate the role of Tipα in promoting infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 47 publications
(65 reference statements)
0
10
0
Order By: Relevance
“…Our data establishe that HpaA stimulation results in a 1.3-fold increase in TNF-α cytokine induction in AGS cells and a 2.8-fold increase in macrophage cells. Significantly, this response closely mirrors the positive control reaction triggered by the TNF-α inducing protein, Tipα, a bacterial effector utilized by H. pylori to sustain chronic inflammation in gastric tissues ( 39 ). Furthermore, we detect additional IL8 responses in macrophages upon HpaA stimulation, demonstrating once again comparable response to the Tipα effector.…”
Section: Resultsmentioning
confidence: 75%
“…Our data establishe that HpaA stimulation results in a 1.3-fold increase in TNF-α cytokine induction in AGS cells and a 2.8-fold increase in macrophage cells. Significantly, this response closely mirrors the positive control reaction triggered by the TNF-α inducing protein, Tipα, a bacterial effector utilized by H. pylori to sustain chronic inflammation in gastric tissues ( 39 ). Furthermore, we detect additional IL8 responses in macrophages upon HpaA stimulation, demonstrating once again comparable response to the Tipα effector.…”
Section: Resultsmentioning
confidence: 75%
“…HQJZD may inhibit H. pylori activity by regulating lipids and atherosclerotic pathways. Both TNF-α and NF-κB play key roles in inflammation and cancer development, and the H. pylori -specific virulence factor, Tip-α, is a TNF-α-inducing protein that participates in TNF-α and NF-κB pathways as an oncogenic factor mediating inflammation and immune responses, and has an important part in triggering chronic gastritis, hyperplasia, and gastric cancer ( Morningstar-Wright et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In human macrophages, the hypothetical protein 1173 (HP1173) from H. pylori strain 26695 stimulates the MAPK signaling pathways, leading to the activation of NF-κB and activator protein-1 (AP-1), and thus to the secretion of TNF-α, chemokine C-X-C motif chemokine ligand 8 (CXCL8) and IL-1β [ 35 ]. In a murine model, it was found that the TNF-α-inducing protein (Tip α) of H. pylori activates the NF-κB signaling pathway, and contributes to the pro-inflammatory response, gastritis development, hyperplasia, and gastric cancer [ 36 ]. Moreover, H. pylori CagA reduces the secretion of IL-12p40, and increases the expression of IL-10, which shows pro- and anti-inflammatory effects, promoted by this oncoprotein [ 37 ].…”
Section: Discussionmentioning
confidence: 99%